2020
DOI: 10.1155/2020/7353618
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella sorokiniana Extract Prevents Cisplatin-Induced Myelotoxicity In Vitro and In Vivo

Abstract: Cisplatin chemotherapy causes myelosuppression and often limits treatment duration and dose escalation in patients. Novel approaches to circumvent or lessen myelotoxicity may improve clinical outcome and quality of life in these patients. Chlorella sorokiniana (CS) is a freshwater unicellular green alga and exhibits encouraging efficacy in immunomodulation and anticancer in preclinical studies. However, the efficacy of CS on chemoprotection remains unclear. We report here, for the first time, that CS extract (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Lycopene isolated from chlorella inhibited the growth of prostate cancer cells in [64]. In an animal model, chlorella extract reduced bone marrow suppression caused by cisplatin [8]. Clinical data on chlorella treatment include only a small group of breast cancer patients [31].…”
Section: Chlorellamentioning
confidence: 99%
“…Lycopene isolated from chlorella inhibited the growth of prostate cancer cells in [64]. In an animal model, chlorella extract reduced bone marrow suppression caused by cisplatin [8]. Clinical data on chlorella treatment include only a small group of breast cancer patients [31].…”
Section: Chlorellamentioning
confidence: 99%
“…This fraction showed typical signals of fatty acids as analyzed by 1 H-and 13 C-NMR spectra (Chou et al, 2008). Most recently, Lin et al reported that Chlorella sorokiniana (W87) extract prevented cisplatin-induced myelotoxicity in vitro and in vivo, however, the main components were unrevealed (Lin et al, 2020). Yun and colleagues also reported that Chlorella sorokiniana KNUA114, which was collected from Ulleung Island South Korea, was rich in fatty acids and might potentially be used as biological resources (Yun et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Влияние приема хлореллы на уменьшение накопления кадмия, качество жизни больных раком молочной железы, эффективность в иммуномодуляции рассмотрено в работах зарубежных ученых [17][18][19].…”
Section: Introductionunclassified